2021
DOI: 10.1002/btm2.10265
|View full text |Cite
|
Sign up to set email alerts
|

A ferret brain slice model of oxygen–glucose deprivation captures regional responses to perinatal injury and treatment associated with specific microglial phenotypes

Abstract: Organotypic brain slice models are an ideal technological platform to investigate therapeutic options for hypoxic‐ischemic (HI) brain injury, a leading cause of morbidity and mortality in neonates. The brain exhibits regional differences in the response to HI injury in vivo. This can be modeled using organotypic brain slices, which maintain three‐dimensional regional structures and reflect the regional differences in injury response. Here, we developed an organotypic whole hemisphere (OWH) slice culture model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 65 publications
(97 reference statements)
0
7
0
Order By: Relevance
“…To study EV therapeutic activity and its impact on cellular behavior, we performed oxygen glucose deprivation (OGD) in organotypic whole hemisphere (OWH) slices from the P10 rat brain to model HI in term-equivalent neonates [ 32 , 33 ]. OWH brain slices uniquely capture the 3D cytoarchitecture and regional complexity of the brain [ 33 , 34 ]. OWH slices allow for the simultaneous assessment of different brain regions, such as the cortex, hippocampus, thalamus, and others, which are not present collectively in standard organoid, cortical, or hippocampal culture models [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To study EV therapeutic activity and its impact on cellular behavior, we performed oxygen glucose deprivation (OGD) in organotypic whole hemisphere (OWH) slices from the P10 rat brain to model HI in term-equivalent neonates [ 32 , 33 ]. OWH brain slices uniquely capture the 3D cytoarchitecture and regional complexity of the brain [ 33 , 34 ]. OWH slices allow for the simultaneous assessment of different brain regions, such as the cortex, hippocampus, thalamus, and others, which are not present collectively in standard organoid, cortical, or hippocampal culture models [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…BEV solution was then diluted with sterile 1X PBS to achieve experimental dosages (5 μg, 12.5 μg, 25 μg, 50 μg) suspended in a total volume of 100 μL per slice. The BEV solution was topically applied onto the tissue slices at various application timepoints (−24, 0, 4, and 24 h post-OGD conditioning), aligned with previous therapeutic efficacy studies performed in OWH slices [ 33 , 34 ]. After various BEV exposure timepoints of interest (4, 24, and 48 h), slices were stained with propidium iodide (PI) to quantify cell viability and fixed with 4% formalin.…”
Section: Methodsmentioning
confidence: 99%
“…We leverage PI, a fluorescence-based imaging approach for quantifying cell damage [ 35 , 36 ], to characterize how both the cortical and striatal regions of P10 and P17 OWH slices respond to the transition ex vivo. The cortex and striatum play critical roles in normal brain function [ 37 – 40 ] and are susceptible to hypoxic-ischemic events like cerebral ischemia [ 41 43 ], which we model using OGD.…”
Section: Resultsmentioning
confidence: 99%
“…The primary goal of the studies presented here was to examine regional and sex-based differences in cell death as a result of OGD and vitamin E treatment. However, we have previously shown that regional differences in treatment response are linked to local microglial responses to injury [40]. This may be a plausible reason for why the hippocampus, one of the brain regions most densely populated with microglia [41], showed a significant decrease in cytotoxicity after vitamin E exposure post-injury.…”
Section: Discussionmentioning
confidence: 99%